Structural Reinforcement through Liquid Encapsulation. Issue 2 (2nd December 2016) - Chipara, Alin Cristian; Owuor, Peter Samora; Bhowmick, Sanjit; Brunetto, Gustavo; Asif, S. A. Syed; Chipara, Mircea; Vajtai, Robert; Lou, Jun; Galvao, Douglas S.; Tiwary, Chandra Sekhar; Ajayan, Pulickel M.
Abstract : The liquid inside a solid material is one of the most common composite materials in nature. The interface between solid–liquid plays an important role in unique deformation. Here, model systems of two polymers (polydimethylsiloxane–polyvinylidenefluoride) are used to make sphere of solid with liquid inside it.